59.7k views
4 votes
Simply (i+4)+(2i-3)

what’s the answer to this??

User Longneck
by
5.3k points

2 Answers

4 votes
i x 2i = 3i i x -3 = -3i 4 x 2i = 8i. 4 x -3 = -12 so 3i + -3i + 8i = 8i-12. 8i + -12 is the answer
User Kenaniah
by
5.0k points
3 votes

Answer:

Im not entirely sure, but i believe its 3i+1

Explanation:

(i+2i)+(4-3)=

3i + 1

(you collect the like terms, and add them up together! it's that simple!)

User Gelya
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.